Potential Study of Tidal Stream Turbine Farm at Toyapakeh Strait, Bali - Alamsyah Kurniawan; Prayla Putri Annani Barli; Munawir Bintang Pratama; Ahmad Fitriadhy (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2021)
In 2015, Bali Province is mandated by ESDM ministry to become the National Region of Clean Energy, promoting efforts to explore new source of electricity namely tidal stream energy. Previous works have demonstrated that Toyapakeh Strait contains a promising tidal stream resource, with a high stream in a long period. In this study, hydrodynamic modelling and power production analysis is conducted to evaluate this potential with an aim to meet energy demand of Tiga Nusa Cluster Islands. Twenty-one Gen5 KHPS turbines are employed in this study, at an optimized location, 8.72°S, 115.44°E, which contains the highest energy potential. Financial analysis, with 25-year return period of investment and 3.60% interest rate, resulting levelized cost of energy (LCOE) of Rp 6,100.kWh-1. This value is higher than the national and regional selling nominal, in other word the energy cost of tidal stream turbine is relatively high in this location. Nearly 46% of energy cost is spent for turbine fabrication, and from the sensitivity analysis, cutting half the turbine costs may reduce the price by Rp 1,400.kWh-1 while increasing the amount of installed turbine is less significant. Despite of the high prices, the study shows that Toyapakeh Strait holds a promising resource of tidal stream energy.